Planar elliptical solid immersion lens based on a Cartesian oval - Donegan, John; Mc Closkey, David (My University, 2013)
We report on the design of a single element planar solid immersion lens which is theoretically capable of confining light to a focal spot with full width half maximum of 0.29 λ (154 nm at λ = 532 nm) and achieving an effective numerical aperture of 1.732. Devices are fabricated and initial optical characterization is performed using a far-field imaging technique providing a lower bound on the numerical aperture of 0.7. Experimental results compare well with two dimensional finite element method simulations. Devices can be mass produced using ultraviolet lithography and produce focal volumes lower than expensive microscope objectives.
PUBLISHED
cited by 1
Keywords: Nonlinear acoustics; Interface structure; Light scattering; Acoustic noise rating; Apertures